A novel deodorization method of edible oil by using ethanol steam at low temperature. Issue 2 (18th January 2021) - Yang, Chen; Wang, Chengming; Wang, Man; Qin, Xiaoyu; Hao, Guifang; Kang, Mengjie; Hu, Xizhou; Cheng, Yunbin; Shen, Jing
Abstract : Abstract: A novel deodorization method of edible oil by using ethanol steam at low‐temperature was developed. We compared the chemical changes in predeodorized rapeseed oil after anhydrous ethanol steam distillation at low temperature (140 to 220 °C) (L‐ESD) and conventional high‐temperature (250 °C) water‐steam distillation (H‐WSD) in terms of odor characteristics, physicochemical properties, micronutrient contents, antioxidant performance, and fatty acid composition. Compared with H‐WSD (250 °C for 60 min), L‐ESD at 180 °C for 80 to 100 min resulted in lower response values of electronic nose, free fatty acid (0.03% to 0.07%), and peroxide value (0.00 to 0.67 meq/kg), but higher retention of tocopherols (554.93 to 551.59 mg/kg), total phenols (43.36 to 45.42 mgGAE/kg), total carotenoids (65.78 to 67.85 mg/kg), phytosterols (585.80 to 596.53 mg/100 g), polyunsaturated fatty acids (27.95 to 28.01%), and better antioxidant properties. In conclusion, L‐ESD can mitigate the damage of oil and thus significantly improve the safety of vegetable oils with a high retention of nutrients compared with conventional H‐WSD. Practical Application: The present study aimed to compare the chemical changes in predeodorized rapeseed oil after anhydrous ethanol steam distillation at low temperature (140 to 220 °C) (L‐ESD) and conventional high‐temperature (250 °C) water‐steam distillation (H‐WSD) in terms of odor characteristics, physicochemical properties, micronutrient contents, antioxidant performance, and fatty acid composition. Results indicated that this finding supplies a theoretical basis for developing a method with retaining more micronutrients and producing less harmful substances for the deodorization of rapeseed oil.